Childhood Acute B-Lineage Lymphoblastic Leukemia With CDKN2A/B Deletion Is a Distinct Entity With Adverse Genetic Features and Poor Clinical Outcomes - Feng, Jing; Guo, Ye; Yang, Wenyu; Zou, Yao; Zhang, Li; Chen, Yumei; Zhang, Yingchi; Zhu, Xiaofan; Chen, Xiaojuan (Frontiers in Oncology, 2022)
To further emphasize the clinical-genetic features and prognosis of CDKN2A/B deletions in childhood acute lymphoblastic leukemia (ALL), we analyzed retrospectively 819 consecutive B-ALL patients treated with Chinese Children’s Cancer Group ALL-2015(CCCG-ALL-2015) protocol, and FISH analysis on CDKN2A/B deletion was available for 599 patients. The prevalence of CDKN2A/B gene deletions was 20.2% (121/599) of B-ALL. CDKN2A/B deletions were significantly associated with older age, higher leukocyte counts, a higher percentage of hepatosplenomegaly, and a higher frequency of BCR-ABL(P<0.05). Those patients achieved similar MRD clearance and complete remission compared to patients without CDKN2A/B deletion. The CDKN2A/B deletions were correlated with inferior outcomes, including a 3-year event-free survival (EFS) rate (69.8±4.6 vs. 89.2±1.6%, P=0.000), 3-year overall survival (OS) rate (89.4%±2.9% vs. 94.7%±1.1%, P=0.037). In multivariable analysis, CDKN2A/B deletion was still an independent prognostic factor for EFS in total cohorts (P<0.05). We also detected a multiplicative interaction between CDKN2A/B deletions and TP53 deletion on dismal prognosis (P-interaction<0.05). In conclusion, CDKN2A/B deletion is associated with distinct characteristics and serves as a poor prognostic factor in pediatric ALL, especially in TP53 deletion carriers.